Injection Injury Caused by Disinfectant During COVID-19: A Case Report - Shi, Haifei; Liang, Kejiong; Ali, Rizwan; Xu, Shengquan; Ding, Shili (Frontiers in Public Health, 2022)
High-pressure injection injury of the hand is a rare but severe emergency, which requires full attention and timely treatment. However, the early symptoms may not be obvious. As the swelling and necrosis progress, the condition gradually worsens, and in severe cases, it may end with amputation. We report a particular case of a hand injection injury, which occurred to a worker who worked overtime to produce disinfectant during the COVID-19 pandemic. Because of the chemical toxicity of the disinfectant and pressure’s damage, although the emergency debridement was promptly performed, we still lost some fingers in the end. In the existing disinfection product manuals, we have not seen any tips on dealing with tissue injection injury. It may reduce workers' attention to injuries, leading to delays in emergency operations.